T regulatory cells metabolism: The influence on functional properties and treatment potential - Tomaszewicz, Martyna; Ronowska, Anna; Zieliński, Maciej; Jankowska-Kulawy, Agnieszka; Trzonkowski, Piotr (Frontiers in Immunology, 2023)
CD4+CD25highFoxP3+ regulatory T cells (Tregs) constitute a small but substantial fraction of lymphocytes in the immune system. Tregs control inflammation associated with infections but also when it is improperly directed against its own tissues or cells. The ability of Tregs to suppress (inhibit) the immune system is possible due to direct interactions with other cells but also in a paracrine fashion via secretion of suppressive compounds. Today, attempts are made to use Tregs to treat autoimmune diseases, allergies, and rejection after bone marrow or organ transplantation. There is strong evidence that the metabolic program of Tregs is connected with the phenotype and function of these cells. A modulation towards a particular metabolic stage of Tregs may improve or weaken cells’ stability and function. This may be an important tool to drive the immune system keeping it activated during infections or suppressed when autoimmunity occurs.